Experimental Investigations on Flexural Behaviour of Self Compacting Concrete Beam with Silica Fume. Issue 1 (April 2021) - Rajendra Prasath, C.; Vivek, D.; Elango, K. S; Dharmaraj, R.
Abstract: The proposed investigational programme aims to assess SCC efficiency by altering the percentage of silica fumes used as a substitute material. A study of the reliability of fresh and hardened concrete properties was conducted. In this study, the test mix which really compensates the fresh concrete properties provides the highest compressive strength was used. Silica fume is used to substitute cement in varying percentages (0, 10%, 15% and 20%). As compared to other cement replacement, Self-Compacting Concrete with 15% silica fume showed higher performance. Three beams were cast and assessed for flexural behaviour: conventional RCC, self-compacting concrete Beam, and SCC with 15% silica fume. As compared to other instances, SCC with 15% silica fume performed well, which is shown in the load deflection graph.